Hubungan Ukuran Lingkar Pinggang terhadap Kekuatan Genggaman Tangan pada Pria dengan Pekerjaan Aktivitas Fisik Tinggi - Irfan Darfika Lubis; Putri Susriza Khairani (Universitas Muhammadiyah Manado, 2026)
Background: Hand grip strength is an essential indicator of physical capacity and nutritional status that can identify obesity risk. Adipose tissue accumulation in central obesity contributes to decreased hand grip strength quality through impaired muscle force transmission. Previous studies showed inconsistent results regarding the relationship between waist circumference and hand grip strength, especially in populations with high physical activity. Objective: To analyze the relationship between waist circumference and hand grip strength in male construction workers with high physical activity in Medan City. Methods: This descriptive-analytic study with cross-sectional design involved 100 male construction workers aged 30-39 years selected using purposive sampling technique. Waist circumference was measured using measuring tape, while hand grip strength was measured using handgrip dynamometer. Data analysis used Chi-Square test with significance level α=0.05. Results: The majority of respondents had normal waist circumference (64%) with mode 70 cm and normal grip strength category (53%) with mode 41.7 kg. Chi-Square test showed significant relationship between waist circumference and hand grip strength (p=0.039). Conclusion: There is a significant relationship between waist circumference and hand grip strength in construction workers. High physical activity does not completely prevent central obesity, therefore nutritional management and health education programs are needed for optimization of body composition and muscle functional capacity.